Labour in the Transition to Circular Economy - Guillibert, Paul (2024)
The Circular Economy (CE) is an economic project based on object design, reuse, recycling and transformation that aims to limit the extraction of resources, waste and pollution to a minimum. It is a mode of production that seeks to respond to the challenges of the Anthropocene, namely global warming and the ecological crisis. Nevertheless, it is not always obvious to what extent CE practices and models take into account the social aspects of transitioning, in terms of decent wages or working conditions for a dignified and healthy life. In this chapter, we aim to show the importance of the perspective of labour to design circularity. Recent Just Transition (JT) literature, on the other hand, emphasizes how workers themselves can lead or design social transformation from a CE perspective, creating high-quality employment. This is a social justice requirement in line with both JT as demanded by workers’ organisations and international trade unions, and Sustainable Development Goals (SDGs) as preached by the United Nations. On the one hand, CE could benefit from workers’ knowledge about productive processes. On the other hand, a marginalisation of labourers would put CE at risk of entrenching – if not deepening – social inequalities. Thus, rethinking CE from the perspective of workers implies respecting five fundamental pillars of the JT: 1) Maintaining a high level of employment (quantitative approach); 2) Ensuring decent jobs and wages (qualitative approach); 3) Taking into account the capability of workers themselves to design CE-inspired labour processes (subjective approach); 4) Rethinking CE models from the perspective of women's informal or unpaid subsistence work (feminist approach); 5) Including to migrants, racially discriminated people and noncitizens in the composition of the workforce (decolonial approach).